SISTEM VALIDASI TAGIHAN BIAYA DARI PENYEDIA LAYANAN KOMUNIKASI DATALINK MENGGUNAKAN SKYWISE PADA PT. GARUDA INDONESIA - Masayu Heppy Sharhana, (2021)
The Validation System is a development of information technology in the aviation industry to support an airline in carrying out business processes in accordance with good corporate governance (GCG). Its function can be adapted to the needs of an airline. The purpose of this research and design is to produce an AIRCOM Datalink Data Analysis and Invoice Validation System from a Datalink Communication Service Provider that can manage and calculate AIRCOM Datalink data on an airline. Validation system is designed using Laravel framework, PHP and HTML programming languages and Bootstrap for system display. The Validation System can display the results of calculating the use of Datalink communication services so that the bill validation process is easier to do.